Menanamkan Jiwa Kewirausahaan melalui Percontohan Budidaya Tanaman Pangan pada Anak Usia Sekolah di Kabupaten Minahasa Utara - Verra E. J. Mawitjere; Revolson A. Mege; Julduz R. Paus; Jeane Mantiri; Mokosuli Y. Semuel (DEDIKASI, 2019)
A community service activity through the Community Empowerment program (KKN PPM) to improve school-age children's entrepreneurship skills and knowledge in Likupang Barat has been well implemented. The KKN PPM program aims to produce an action program for food crop cultivation by utilizing the schoolyard in an effort to instill the entrepreneurial spirit in school-age children and increase knowledge and skills in life skills through pilot projects of cultivation of food crops for school-age children in SMPN 1 Talise. The method used in the KKN PPM program was a combination of "application of science and technology appropriately" in cultivation of food crops with the "Pilot Project" learning approach or demonstration of farming by utilizing the schoolyard. Therefore, the children get life skill experience in the effort to characterize entrepreneurship. Moreover, this activity becomes a laboratory and learning resource for students of the Economic Education subjects as well as child character development. The results achieved in this program were the availability of the piloting food crops that can support the fulfillment of consumption needs. In addition, it can be used as a learning media for the Economic Education subject in an effort to instill an entrepreneurial spirit, as well as a source of school needs for school-aged children.